A method for preparing highly transparent high borosilicate glass
The preparation of rare earth chloride-treated silica and added phosphorus-modified lithium oxide flux by aerogel method, and the preparation of high borosilicate glass by float method solves the shortcomings of existing high borosilicate glass in terms of hardness, fracture toughness and optical properties, and achieves higher mechanical properties and excellent optical properties.
Patent Information
- Application Number
- CN202411884539.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-20
AI Technical Summary
While improving the processing performance, existing borosilicate glasses have shortcomings in hardness, fracture toughness and optical properties, especially the problems of reduced transparency and optical deformation.
The rare earth chloride-treated silica was prepared by aerogel method, and combined with the addition of phosphorus-modified lithium oxide flux, high borosilicate glass was prepared by float method.
The hardness, fracture toughness and impact resistance of the glass are significantly improved, while reducing the expansion coefficient, maintaining high transparency and reducing optical deformation.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing highly transparent high-borosilicate glass, and belongs to the field of high-borosilicate glass manufacturing. Background Art
[0002] With the development of electronics, biology, security, new energy, building fire protection and aerospace, higher requirements are put forward for glass materials related to various fields. At present, glass is developing in the direction of multiple specifications, multiple functions, large size, large scale and high quality. Compared with soda-lime-silicon glass, high borosilicate glass has many excellent properties due to its special components and has greater development space. Countries around the world have also invested more financial and material resources in the research and development of high borosilicate glass.
[0003] High borosilicate glass is mainly divided into two categories: borosilicate glass without alkali metal oxides and alkali-containing borosilicate glass. Alkali-containing borosilicate glass is mostly used in fibers, sealants, optical and photochromic components of structural composite materials, while borosilicate glass systems without alkali metal oxides are more suitable for substrates of flat panel displays.
[0004] The alkali metal oxides in the alkali borosilicate glass act as network exosomes in the glass structure, which can provide free oxygen, increase a certain number of bridging oxygen bonds, and increase the number of bridging oxygen, thereby playing a role in accumulating the glass network skeleton. On the other hand, the alkali metal oxides act as fluxing agents, which can reduce the viscosity of the glass melt and thereby improve the processing properties of the glass.
[0005] Commonly used alkali metal oxides in high borosilicate glass include sodium oxide, magnesium oxide, calcium oxide, etc. However, these commonly used alkali metal oxides all have the same defect, that is, although they are effective in reducing the viscosity of glass melt, as their proportion in the glass component increases, the thermal expansion coefficient of the glass will increase, and the microhardness of the glass will also decrease.
[0006] Studies have shown that using lithium oxide instead of commonly used alkali metal oxides can greatly improve the processing performance of glass. As a strong flux, its bond-breaking effect can accelerate the melting of glass. In addition, adding lithium oxide to the glass system can also increase the density of the glass network structure, which has a positive effect on improving the hardness and fracture toughness of the glass, and at the same time reduces the expansion coefficient.
[0007] However, lithium oxide is achieved by increasing the number of crystals inside the glass, that is to say, the higher the crystal content inside the glass, the more effectively it can prevent the expansion of cracks, and the more obvious its toughening effect will be. However, at the same time, it will cause the transparency of the glass to decrease and cause optical deformation of the glass. When the incident angle is too large, it will affect people's judgment of the position and outline of objects behind the glass, and the optical performance will be poor. Summary of the invention
[0008] The technical problem to be solved by the present invention is to overcome the defects of the prior art, use the aerogel method to prepare rare earth chloride treated silica as a silicon source for a part of the glass, combine with the addition of phosphorus modified lithium oxide flux, and finally prepare high borosilicate glass, thereby improving the hardness and fracture toughness of the glass, reducing the expansion coefficient of the glass, and at the same time curbing the reduction of the optical properties of the glass, especially the reduction of transparency, and reducing the optical deformation of the glass.
[0009] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0010] A method for preparing highly transparent high-borosilicate glass comprises preparing rare earth chloride treated silicon dioxide by an aerogel method, preparing phosphorus modified lithium oxide flux, and preparing glass by a float method.
[0011] The following are further improvements to the above technical solution:
[0012] The method for preparing rare earth chloride treated silica by the aerogel method comprises: mixing tetraethyl orthosilicate, deionized water and anhydrous ethanol, stirring until the mixture stops evenly to obtain a mixed solution, then adjusting the pH of the mixed solution to 3.0-3.2 with a hydrochloric acid solution, performing hydrolysis for 180-210 minutes, and after the hydrolysis is completed, adjusting the pH to 8.6-8.9 with solid sodium carbonate, and then adding the rare earth chloride mixed solution, stirring for 75-100 minutes to obtain a wet gel, and then controlling the temperature to 40-45° C., aging the wet gel for 51.5-52.5 hours, and after the aging is completed, drying the wet gel at 120° C. for 8 hours, and then controlling the temperature to 740-760° C., calcining the dried wet gel for 130-150 minutes, and cooling to room temperature after the calcination is completed to obtain rare earth chloride treated silica;
[0013] The mass ratio of the mixed solution of tetraethyl orthosilicate, deionized water, anhydrous ethanol and rare earth chloride is 85-115:70-80:700-800:2.5-3.5;
[0014] In the rare earth chloride mixed solution, the concentration of lanthanum is 0.20-0.30 mol / L, the concentration of cerium is 0.20-0.30 mol / L, the concentration of praseodymium is 0.08-0.12 mol / L, and the rest is water;
[0015] The concentration of the hydrochloric acid solution is 0.9-1.1 mol / L;
[0016] The particle size of the rare earth chloride treated silicon dioxide is 150-200 nm.
[0017] The method for preparing a phosphorus-modified lithium oxide flux comprises: mixing nano lithium oxide with an ethanol aqueous solution, stirring to make it dispersed evenly, obtaining a lithium oxide dispersion, then adding phenylaminomethyl triethoxysilane to the lithium oxide dispersion, controlling the temperature to be 61-67° C., stirring for 7.5-8.5 hours, filtering, washing, and drying after the stirring is completed to obtain amino-treated nano lithium oxide, then mixing the amino-treated nano lithium oxide and p-hydroxybenzaldehyde, controlling the temperature to be 68-74° C., stirring for 5.5-6.5 hours, adding diethyl phosphite after the stirring is completed, keeping the temperature unchanged, and continuing to stir for 3.5-4.5 hours, and finally filtering, washing, and drying to obtain a phosphorus-modified lithium oxide flux;
[0018] The mass ratio of the nano lithium oxide to the ethanol aqueous solution is 1:6.5-7.5;
[0019] The concentration of the ethanol aqueous solution is 65-75wt%;
[0020] The mass ratio of the lithium oxide dispersion to anilinomethyltriethoxysilane is 45-55:3;
[0021] The mass ratio of the amino-treated nano lithium oxide, p-hydroxybenzaldehyde and diethyl phosphite is 4.5-5.5:2.8-3.2:0.9-1.1.
[0022] The float process for preparing glass comprises the following steps: uniformly mixing matrix silicon dioxide, rare earth chloride treated silicon dioxide, boron oxide, phosphorus modified lithium oxide flux, aluminum oxide, sodium oxide, magnesium oxide and zirconium oxide, controlling the temperature to be 1750-1780°C, firing for 60-75 minutes, using a platinum stirring rod to remove bubbles during the firing process, obtaining molten glass liquid after firing, pouring the molten glass liquid into a mold for molding to obtain a molded glass blank, controlling the temperature to be 605-625°C, annealing the molded glass blank for 145-155 minutes to obtain an annealed glass blank, controlling the temperature to be 685-705°C, crystallizing the annealed glass blank for 11.5-12.5 hours, and naturally cooling the annealed glass blank to room temperature along with the furnace after crystallization to obtain a highly transparent high borosilicate glass.
[0023] The mass ratio of the matrix silicon dioxide, rare earth chloride treated silicon dioxide, boron oxide, phosphorus modified lithium oxide flux, aluminum oxide, sodium oxide, magnesium oxide and zirconium oxide is 575-625:125-175:130-140:14-16:21-25:14-16:7.5-8.5:6.5-7.5;
[0024] The particle size of the matrix silicon dioxide is 4-6 μm.
[0025] Compared with the prior art, the present invention achieves the following beneficial effects:
[0026] The high borosilicate glass prepared by the present invention has relatively excellent mechanical properties. According to the method in GB / T37781-2019, the bending strength of the glass is tested, and the bending strength is 193-197 MPa; according to the method in GB / T37780-2019, the elastic modulus and shear modulus of the glass are tested, and the elastic modulus is 75-75 GPa, and the shear modulus is 5.17-5.25 GPa; according to the method in GB / T37900-2019, the fracture toughness of the glass is tested, and the fracture toughness is 4.23-4.40 MPa·m 1 / 2 ; According to the method in GB / T39814-2021, the impact resistance of glass is tested, and the maximum impact height is 1750-1800mm;
[0027] The high borosilicate glass prepared by the present invention has good water resistance. According to the method in GB / T34843-2017, the water resistance grade of the glass is tested, wherein the water resistance grade of the 121°C particle method is grade 1, and the water resistance grade of the 98°C particle method is grade HGB1;
[0028] The high borosilicate glass prepared by the present invention has excellent optical properties, not only has high light transmittance, but also does not undergo optical deformation at a larger incident angle. According to the method in GB / T2680-2021, the visible light transmittance and total solar energy transmittance of the glass sample are tested, and the visible light transmittance is 98.5-98.8%, and the total solar energy transmittance is 98.7-99.2%; according to the method in GB / T34185-2017, the incident angle when the glass undergoes optical deformation at a distance of 4.5 m is tested, and the incident angle is 157-165°;
[0029] The high borosilicate glass prepared by the present invention has high hardness and strong scratch resistance. According to the method in GB / T32057-2015, the Vickers hardness of the glass is tested by a hardness tester, and the hardness is 7.04-7.11. The critical load force of the glass scratch resistance is tested by a scratch tester, and the critical load force is 67-72N.
[0030] The high borosilicate glass prepared by the present invention has good thermal properties. According to the method in GB / T16920-2015, the average linear thermal expansion coefficient of the glass is tested, and the average linear thermal expansion coefficient is (1.8-2.2)×10 -7 According to the method in T / ZBH009-2019, the thermal shock resistance of the glass was tested, with the maximum thermal shock resistance temperature difference as the test index, and the thermal shock resistance temperature difference was 445-455℃. DETAILED DESCRIPTION Example 1
[0031] (1) Preparation of rare earth chloride treated silica by aerogel method
[0032] TEOS, deionized water and anhydrous ethanol are mixed and stirred until the mixture stops uniformly to obtain a mixed solution, and then the pH of the mixed solution is adjusted to 3.1 with a hydrochloric acid solution, and hydrolysis is performed for 200 minutes. After the hydrolysis is completed, the pH is adjusted to 8.8 with solid sodium carbonate, and then a rare earth chloride mixed solution is added and stirred for 90 minutes to obtain a wet gel, and then the temperature is controlled to 42°C, and the wet gel is aged for 52 hours. After the aging is completed, the wet gel is dried at 120°C for 8 hours, and then the temperature is controlled to 750°C, and the dried wet gel is calcined for 140 minutes. After the calcination is completed, it is cooled to room temperature to obtain rare earth chloride-treated silica;
[0033] The mass ratio of the mixed solution of tetraethyl orthosilicate, deionized water, anhydrous ethanol and rare earth chloride is 100:75:750:3;
[0034] In the rare earth chloride mixed solution, the concentration of lanthanum is 0.25 mol / L, the concentration of cerium is 0.25 mol / L, the concentration of praseodymium is 0.10 mol / L, and the rest is water;
[0035] The concentration of the hydrochloric acid solution is 1 mol / L;
[0036] The particle size of the rare earth chloride treated silica is 170 nm.
[0037] (2) Preparation of phosphorus-modified lithium oxide flux
[0038] The nano lithium oxide is mixed with an ethanol aqueous solution, stirred to be uniformly dispersed, and a lithium oxide dispersion is obtained. Then, phenylaminomethyl triethoxysilane is added to the lithium oxide dispersion, the temperature is controlled to be 64° C., and the stirring is performed for 8 hours. After the stirring is completed, the nano lithium oxide treated with amino is obtained by filtering, washing, and drying. Then, the nano lithium oxide treated with amino and p-hydroxybenzaldehyde are mixed, the temperature is controlled to be 71° C., and the stirring is performed for 6 hours. After the stirring is completed, diethyl phosphite is added, the temperature is kept unchanged, and the stirring is continued for 4 hours. Finally, the phosphorus-modified lithium oxide flux is obtained by filtering, washing, and drying.
[0039] The mass ratio of the nano lithium oxide to the ethanol aqueous solution is 1:7;
[0040] The concentration of the ethanol aqueous solution is 70wt%;
[0041] The mass ratio of the lithium oxide dispersion to anilinomethyltriethoxysilane is 50:3;
[0042] The mass ratio of the amino-treated nano lithium oxide, p-hydroxybenzaldehyde and diethyl phosphite is 5:3:1.
[0043] (3) Float glass production
[0044] The matrix silica, rare earth chloride treated silica, boron oxide, phosphorus modified lithium oxide flux, aluminum oxide, sodium oxide, magnesium oxide and zirconium oxide are mixed evenly, the temperature is controlled to be 1755°C, and the firing is carried out for 70 minutes. During the firing process, a platinum stirring rod is used to eliminate bubbles. After firing, a molten glass liquid is obtained, and then the molten glass liquid is poured into a mold to form a molded glass blank. The temperature is controlled to be 615°C, and the molded glass blank is annealed for 150 minutes to obtain an annealed glass blank. The temperature is then controlled to be 695°C, and the annealed glass blank is crystallized for 12 hours. After the crystallization is completed, the annealed glass blank is naturally cooled to room temperature with the furnace to obtain a highly transparent high borosilicate glass.
[0045] The mass ratio of the matrix silicon dioxide, rare earth chloride treated silicon dioxide, boron oxide, phosphorus modified lithium oxide flux, aluminum oxide, sodium oxide, magnesium oxide and zirconium oxide is 600:150:135:15:23:15:8:7;
[0046] The particle size of the matrix silicon dioxide is 5 μm. Example 2
[0047] (1) Preparation of rare earth chloride treated silica by aerogel method
[0048] TEOS, deionized water and anhydrous ethanol are mixed and stirred until the mixture stops uniformly to obtain a mixed solution, and then a hydrochloric acid solution is used to adjust the pH of the mixed solution to 3.0, and hydrolysis is performed for 180 minutes. After the hydrolysis is completed, solid sodium carbonate is used to adjust the pH to 8.6, and then a rare earth chloride mixed solution is added and stirred for 100 minutes to obtain a wet gel, and then the temperature is controlled to 40°C, and the wet gel is aged for 52.5 hours. After the aging is completed, the wet gel is dried at 120°C for 8 hours, and then the temperature is controlled to 740°C, and the dried wet gel is calcined for 150 minutes. After the calcination is completed, it is cooled to room temperature to obtain rare earth chloride treated silica;
[0049] The mass ratio of the mixed solution of tetraethyl orthosilicate, deionized water, anhydrous ethanol and rare earth chloride is 85:70:700:2.5;
[0050] In the rare earth chloride mixed solution, the concentration of lanthanum is 0.20 mol / L, the concentration of cerium is 0.20 mol / L, the concentration of praseodymium is 0.08 mol / L, and the rest is water;
[0051] The concentration of the hydrochloric acid solution is 0.9 mol / L;
[0052] The particle size of the rare earth chloride treated silica is 150 nm.
[0053] (2) Preparation of phosphorus-modified lithium oxide flux
[0054] The nano lithium oxide is mixed with an ethanol aqueous solution, stirred to be uniformly dispersed, and a lithium oxide dispersion is obtained. Then, phenylaminomethyl triethoxysilane is added to the lithium oxide dispersion, the temperature is controlled to be 61° C., and stirring is performed for 8.5 hours. After the stirring is completed, the nano lithium oxide treated with amino is obtained by filtering, washing, and drying. Then, the nano lithium oxide treated with amino and p-hydroxybenzaldehyde are mixed, the temperature is controlled to be 68° C., and stirring is performed for 6.5 hours. After the stirring is completed, diethyl phosphite is added, the temperature is kept constant, and stirring is continued for 3.5 hours. Finally, the phosphorus-modified lithium oxide flux is obtained by filtering, washing, and drying.
[0055] The mass ratio of the nano lithium oxide to the ethanol aqueous solution is 1:6.5;
[0056] The concentration of the ethanol aqueous solution is 65wt%;
[0057] The mass ratio of the lithium oxide dispersion to anilinomethyltriethoxysilane is 45:3;
[0058] The mass ratio of the amino-treated nano lithium oxide, p-hydroxybenzaldehyde and diethyl phosphite is 4.5:2.8:0.9.
[0059] (3) Float glass production
[0060] The matrix silica, rare earth chloride treated silica, boron oxide, phosphorus modified lithium oxide flux, aluminum oxide, sodium oxide, magnesium oxide and zirconium oxide are mixed evenly, the temperature is controlled to be 1750°C, and the firing is carried out for 75 minutes. During the firing process, a platinum stirring rod is used to eliminate bubbles. After firing, a molten glass liquid is obtained, and then the molten glass liquid is poured into a mold to form a molded glass blank. The temperature is controlled to be 605°C, and the molded glass blank is annealed for 145 minutes to obtain an annealed glass blank. The temperature is then controlled to be 685°C, and the annealed glass blank is crystallized for 11.5 hours. After the crystallization is completed, the annealed glass blank is naturally cooled to room temperature with the furnace to obtain a highly transparent high borosilicate glass.
[0061] The mass ratio of the matrix silicon dioxide, rare earth chloride treated silicon dioxide, boron oxide, phosphorus modified lithium oxide flux, aluminum oxide, sodium oxide, magnesium oxide, and zirconium oxide is 575:125:130:14:21:14:7.5:6.5;
[0062] The particle size of the matrix silicon dioxide is 4 μm. Example 3
[0063] (1) Preparation of rare earth chloride treated silica by aerogel method
[0064] TEOS, deionized water and anhydrous ethanol are mixed and stirred until the mixture stops uniformly to obtain a mixed solution, and then a hydrochloric acid solution is used to adjust the pH of the mixed solution to 3.2, and hydrolysis is performed for 210 minutes. After the hydrolysis is completed, solid sodium carbonate is used to adjust the pH to 8.9, and then a rare earth chloride mixed solution is added and stirred for 75 minutes to obtain a wet gel, and then the temperature is controlled to 45°C, and the wet gel is aged for 51.5 hours. After the aging is completed, the wet gel is dried at 120°C for 8 hours, and then the temperature is controlled to 760°C, and the dried wet gel is calcined for 130 minutes. After the calcination is completed, it is cooled to room temperature to obtain rare earth chloride-treated silica;
[0065] The mass ratio of the mixed solution of tetraethyl orthosilicate, deionized water, anhydrous ethanol and rare earth chloride is 85:70:700:2.5;
[0066] In the rare earth chloride mixed solution, the concentration of lanthanum is 0.30 mol / L, the concentration of cerium is 0.30 mol / L, the concentration of praseodymium is 0.12 mol / L, and the rest is water;
[0067] The concentration of the hydrochloric acid solution is 1.1 mol / L;
[0068] The particle size of the rare earth chloride treated silica is 200 nm.
[0069] (2) Preparation of phosphorus-modified lithium oxide flux
[0070] The nano lithium oxide is mixed with an ethanol aqueous solution, stirred to be uniformly dispersed, and a lithium oxide dispersion is obtained. Then, phenylaminomethyl triethoxysilane is added to the lithium oxide dispersion, the temperature is controlled to be 67° C., and the stirring is performed for 7.5 hours. After the stirring is completed, the nano lithium oxide treated with amino is obtained by filtering, washing, and drying. Then, the nano lithium oxide treated with amino and p-hydroxybenzaldehyde are mixed, the temperature is controlled to be 74° C., and the stirring is performed for 5.5 hours. After the stirring is completed, diethyl phosphite is added, the temperature is kept constant, and the stirring is continued for 4.5 hours. Finally, the phosphorus-modified lithium oxide flux is obtained by filtering, washing, and drying.
[0071] The mass ratio of the nano lithium oxide to the ethanol aqueous solution is 1:7.5;
[0072] The concentration of the ethanol aqueous solution is 75wt%;
[0073] The mass ratio of the lithium oxide dispersion to anilinomethyltriethoxysilane is 55:3;
[0074] The mass ratio of the amino-treated nano lithium oxide, p-hydroxybenzaldehyde and diethyl phosphite is 5.5:3.2:1.1.
[0075] (3) Float glass production
[0076] The matrix silica, rare earth chloride treated silica, boron oxide, phosphorus modified lithium oxide flux, aluminum oxide, sodium oxide, magnesium oxide and zirconium oxide are mixed evenly, the temperature is controlled to be 1780°C, and the firing is carried out for 60 minutes. During the firing process, a platinum stirring rod is used to eliminate bubbles. After firing, a molten glass liquid is obtained, and then the molten glass liquid is poured into a mold to form a molded glass blank. The temperature is controlled to be 625°C, and the molded glass blank is annealed for 155 minutes to obtain an annealed glass blank. The temperature is then controlled to be 705°C, and the annealed glass blank is crystallized for 12.5 hours. After the crystallization is completed, the annealed glass blank is naturally cooled to room temperature with the furnace to obtain a highly transparent high borosilicate glass.
[0077] The mass ratio of the matrix silicon dioxide, rare earth chloride treated silicon dioxide, boron oxide, phosphorus modified lithium oxide flux, aluminum oxide, sodium oxide, magnesium oxide, and zirconium oxide is 625:175:140:16:25:16:8.5:7.5;
[0078] The particle size of the matrix silicon dioxide is 6 μm.
[0079] Comparative Example 1
[0080] The difference from Example 1 is that the step of preparing rare earth chloride treated silica by aerogel method is omitted, and in the step of preparing glass by float method, the same amount of base silica is used to replace the original rare earth chloride treated silica, which is used as the raw material component of glass, and the other steps are the same to prepare high borosilicate glass;
[0081] The mass ratio of the matrix silicon dioxide, boron oxide, phosphorus-modified lithium oxide flux, aluminum oxide, sodium oxide, magnesium oxide, and zirconium oxide is 750:135:15:23:15:8:7;
[0082] The particle size of the matrix silicon dioxide is 5 μm.
[0083] Comparative Example 2
[0084] The difference from Example 1 is that the step of preparing phosphorus-modified lithium oxide flux is omitted, and in the step of preparing glass by float process, the same amount of untreated lithium oxide is used to replace the phosphorus-modified lithium oxide flux as the raw material component of glass, and the remaining steps are the same to prepare high borosilicate glass;
[0085] The mass ratio of the matrix silicon dioxide, rare earth chloride treated silicon dioxide, boron oxide, lithium oxide, aluminum oxide, sodium oxide, magnesium oxide and zirconium oxide is 600:150:135:15:23:15:8:7;
[0086] The particle size of the matrix silicon dioxide is 5 μm.
[0087] Test Example 1 Glass Mechanical Properties Test
[0088] The glasses of Examples 1-3 and Comparative Examples 1-2 were tested for bending strength according to the method in GB / T37781-2019;
[0089] According to the method in GB / T37780-2019, the elastic modulus and shear modulus of glass are tested;
[0090] Test the fracture toughness of glass according to the method in GB / T37900-2019;
[0091] Test the impact resistance of glass according to the method in GB / T39814-2021;
[0092] The results are shown in Table 1.
[0093] Table 1
[0094]
[0095] Example 1-3 uses an aerogel method to prepare rare earth chloride treated silica as a silicon source for a portion of the glass, combined with the addition of phosphorus modified lithium oxide flux, to finally prepare high borosilicate glass, which can improve the mechanical properties of the glass, whether it is bending performance, elastic modulus, shear modulus, fracture toughness or impact resistance;
[0096] Comparative Example 1: In the step of preparing rare earth chloride treated silica by the aerogel method, the same amount of matrix silica is used to replace the original rare earth chloride treated silica in the step of preparing glass by the float method to prepare high borosilicate glass, which will cause the mechanical properties of the glass to decrease, especially the bending performance, elastic modulus and fracture toughness to decrease more seriously, and the shear modulus and impact resistance will also decrease to a certain extent;
[0097] In Comparative Example 2, the step of preparing phosphorus-modified lithium oxide flux is omitted. In the float glass preparation step, the same amount of untreated lithium oxide is used instead of the phosphorus-modified lithium oxide flux to prepare high borosilicate glass. This will cause a decrease in the mechanical properties of the glass, especially the shear modulus and impact resistance. In addition, the bending properties, elastic modulus and fracture toughness will also decrease to a certain extent.
[0098] Test Example 2 Glass Water Resistance Test
[0099] The glasses of Examples 1-3 and Comparative Examples 1-2 were tested for water resistance levels according to the method in GB / T34843-2017, including 121°C particle method water resistance and 98°C particle method water resistance. The results are shown in Table 2.
[0100] Table 2
[0101]
[0102] Example 1-3 uses the aerogel method to prepare rare earth chloride treated silica as a silicon source for a part of the glass, combined with the addition of phosphorus modified lithium oxide flux, and finally prepares high borosilicate glass, which can improve the water resistance of the glass. The water resistance level of the 121°C particle method and the 98°C particle method are both high levels;
[0103] Comparative Example 1 omits the step of preparing rare earth chloride treated silica by the aerogel method, and uses the same amount of matrix silica to replace the original rare earth chloride treated silica in the step of preparing glass by the float method to prepare high borosilicate glass, which will cause the water resistance of the glass to decrease. The water resistance of the 121°C particle method and the 98°C particle method are both poor.
[0104] In Comparative Example 2, the step of preparing phosphorus-modified lithium oxide flux is omitted. In the float glass preparation step, the same amount of untreated lithium oxide is used instead of the phosphorus-modified lithium oxide flux to prepare high borosilicate glass, which will cause the water resistance of the glass to decrease. The water resistance of the 121°C particle method and the 98°C particle method are both poor.
[0105] Test Example 3 Glass Optical Performance Test
[0106] The glasses of Examples 1-3 and Comparative Examples 1-2 were tested for visible light transmittance and total solar energy transmittance according to the method in GB / T2680-2021;
[0107] According to the method in GB / T34185-2017, the incident angle when the glass undergoes optical deformation at a distance of 4.5 m was tested. The results are shown in Table 3.
[0108] Table 3
[0109]
[0110] Example 1-3 uses an aerogel method to prepare rare earth chloride treated silica as a silicon source for a portion of the glass, combined with the addition of phosphorus modified lithium oxide flux, to finally prepare high borosilicate glass, which can improve the light transmittance of the glass and can maintain a large angle of incidence without optical deformation;
[0111] Comparative Example 1: In the step of preparing rare earth chloride treated silica by the aerogel method, the same amount of matrix silica is used to replace the original rare earth chloride treated silica in the step of preparing glass by the float method to prepare high borosilicate glass, which will cause the optical properties of the glass to decrease, the visible light transmittance and the total solar energy transmittance to decrease more seriously, and the incident angle when optical deformation occurs is small;
[0112] In Comparative Example 2, the step of preparing phosphorus-modified lithium oxide flux is omitted. In the float glass preparation step, the same amount of untreated lithium oxide is used instead of the phosphorus-modified lithium oxide flux to prepare high borosilicate glass. This will cause the optical properties of the glass to decline, the visible light transmittance and the total solar energy transmittance to decline to a large extent, and the incident angle when optical deformation occurs is extremely small.
[0113] Test Example 4: Glass hardness and scratch resistance test
[0114] The glasses of Examples 1-3 and Comparative Examples 1-2 were tested for Vickers hardness using a hardness tester and for critical load resistance to scratching using a scratch tester according to the method in GB / T32057-2015. The results are shown in Table 4.
[0115] Table 4
[0116]
[0117] Example 1-3 uses an aerogel method to prepare rare earth chloride treated silica as a silicon source for a portion of the glass, combined with the addition of phosphorus modified lithium oxide flux, to finally prepare high borosilicate glass, which can improve the hardness and scratch resistance of the glass;
[0118] Comparative Example 1 omits the step of preparing rare earth chloride treated silica by the aerogel method, and uses the same amount of matrix silica to replace the original rare earth chloride treated silica in the step of preparing glass by the float method to prepare high borosilicate glass, which will cause the hardness of the glass to decrease to a large extent. In addition, the scratch resistance of the glass decreases more seriously, and the critical load force of scratch resistance is small;
[0119] In Comparative Example 2, the step of preparing phosphorus-modified lithium oxide flux is omitted. In the step of preparing glass by the float method, the same amount of untreated lithium oxide is used instead of the phosphorus-modified lithium oxide flux to prepare high borosilicate glass, which will cause the hardness of the glass to decrease to a certain extent. In addition, the scratch resistance of the glass is greatly reduced, and the critical load force for scratch resistance is small.
[0120] Test Example 5 Glass Thermal Performance Test
[0121] The average linear thermal expansion coefficient of the glasses of Examples 1-3 and Comparative Examples 1-2 was tested according to the method in GB / T16920-2015;
[0122] According to the method in T / ZBH009-2019, the thermal shock resistance of the glass was tested, with the maximum thermal shock resistance temperature difference as the test index. The results are shown in Table 5.
[0123] Table 5
[0124]
[0125] Example 1-3 uses an aerogel method to prepare rare earth chloride treated silica as a silicon source for a portion of the glass, combined with the addition of phosphorus modified lithium oxide flux, to finally prepare high borosilicate glass, which can improve the thermal properties of the glass, reduce the expansion coefficient, and have strong thermal shock resistance;
[0126] Comparative Example 1 omits the step of preparing rare earth chloride treated silica by the aerogel method, and uses the same amount of matrix silica to replace the original rare earth chloride treated silica in the step of preparing glass by the float method to prepare high borosilicate glass, which will cause the expansion coefficient of the glass to increase to a large extent. In addition, the thermal shock resistance of the glass decreases more seriously, and the thermal shock resistance temperature difference is small;
[0127] In Comparative Example 2, the step of preparing phosphorus-modified lithium oxide flux is omitted. In the float glass preparation step, the same amount of untreated lithium oxide is used instead of the phosphorus-modified lithium oxide flux to prepare high borosilicate glass, which will cause a serious increase in the expansion coefficient of the glass. In addition, the thermal shock resistance of the glass is greatly reduced, and the thermal shock resistance temperature difference is small.
Claims
1. A method for preparing highly transparent high borosilicate glass, characterized in that: The preparation method includes preparing rare earth chloride treated silicon dioxide by aerogel method, preparing phosphorus modified lithium oxide flux, and preparing glass by float method; The method for preparing rare earth chloride treated silica by aerogel method comprises: mixing tetraethyl orthosilicate, deionized water and anhydrous ethanol, stirring until the mixture stops evenly to obtain a mixed solution, then adjusting the pH of the mixed solution to 3.0-3.2 with a hydrochloric acid solution, performing hydrolysis for 180-210 minutes, and after the hydrolysis is completed, adjusting the pH to 8.6-8.9 with solid sodium carbonate, and then adding the rare earth chloride mixed solution, stirring for 75-100 minutes to obtain a wet gel, and then controlling the temperature to 40-45° C., aging the wet gel for 51.5-52.5 hours, and after the aging is completed, drying the wet gel, and then controlling the temperature to 740-760° C., calcining the dried wet gel for 130-150 minutes, and cooling to room temperature after the calcination to obtain rare earth chloride treated silica; The mass ratio of the mixed solution of tetraethyl orthosilicate, deionized water, anhydrous ethanol and rare earth chloride is 85-115:70-80:700-800:2.5-3.5; In the rare earth chloride mixed solution, the concentration of lanthanum is 0.20-0.30 mol / L, the concentration of cerium is 0.20-0.30 mol / L, the concentration of praseodymium is 0.08-0.12 mol / L, and the rest is water; The method for preparing a phosphorus-modified lithium oxide flux comprises: mixing nano lithium oxide with an ethanol aqueous solution, stirring to make it dispersed evenly, obtaining a lithium oxide dispersion, then adding phenylaminomethyl triethoxysilane to the lithium oxide dispersion, controlling the temperature to be 61-67° C., stirring for 7.5-8.5 hours, filtering, washing, and drying after the stirring is completed to obtain amino-treated nano lithium oxide, then mixing the amino-treated nano lithium oxide and p-hydroxybenzaldehyde, controlling the temperature to be 68-74° C., stirring for 5.5-6.5 hours, adding diethyl phosphite after the stirring is completed, keeping the temperature unchanged, and continuing to stir for 3.5-4.5 hours, and finally filtering, washing, and drying to obtain a phosphorus-modified lithium oxide flux; The mass ratio of the nano lithium oxide to the ethanol aqueous solution is 1:6.5-7.5; The mass ratio of the lithium oxide dispersion to anilinomethyltriethoxysilane is 45-55:3; The mass ratio of the amino-treated nano lithium oxide, p-hydroxybenzaldehyde, and diethyl phosphite is 4.5-5.5:2.8-3.2:0.9-1.1; The float process for preparing glass comprises the following steps: uniformly mixing matrix silicon dioxide, rare earth chloride treated silicon dioxide, boron oxide, phosphorus modified lithium oxide flux, aluminum oxide, sodium oxide, magnesium oxide and zirconium oxide, controlling the temperature to be 1750-1780° C., firing for 60-75 min, stirring to remove bubbles during the firing process, obtaining molten glass liquid after firing, casting the molten glass liquid into a molded glass blank, controlling the temperature to be 605-625° C., annealing the molded glass blank for 145-155 min to obtain an annealed glass blank, controlling the temperature to be 685-705° C., crystallizing the annealed glass blank for 11.5-12.5 h, and naturally cooling the annealed glass blank to room temperature along with the furnace after crystallization to obtain a highly transparent high borosilicate glass; The mass ratio of the matrix silicon dioxide, rare earth chloride treated silicon dioxide, boron oxide, phosphorus modified lithium oxide flux, aluminum oxide, sodium oxide, magnesium oxide and zirconium oxide is 575-625:125-175:130-140:14-16:21-25:14-16:7.5-8.5:6.5-7.
5.
2. The method for preparing a highly transparent borosilicate glass according to claim 1, characterized in that: In the step of preparing rare earth chloride treated silica by the aerogel method, the drying method is to dry the wet gel at 120° C. for 8 hours.
3. The method for preparing a highly transparent high borosilicate glass according to claim 1, characterized in that: In the step of preparing rare earth chloride treated silicon dioxide by the aerogel method, the concentration of the hydrochloric acid solution is 0.9-1.1 mol / L.
4. The method for preparing a highly transparent high borosilicate glass according to claim 1, characterized in that: In the step of preparing rare earth chloride treated silicon dioxide by the aerogel method, the particle size of the rare earth chloride treated silicon dioxide is 150-200nm.
5. The method for preparing a highly transparent borosilicate glass according to claim 1, characterized in that: In the step of preparing the phosphorus-modified lithium oxide flux, the concentration of the ethanol aqueous solution is 65-75wt%.
6. The method for preparing a highly transparent borosilicate glass according to claim 1, characterized in that: In the float glass preparation step, the particle size of the matrix silicon dioxide is 4-6 μm.
Citation Information
Patent Citations
Preparation method of glass and glass film containing rare earth ion doped lanthanum chloride microcrystalline
CN105271766A
Glass film containing rare-earth-ion-doped Cs2LiLuCl6 microcrystalline and preparation method thereof
CN105293944A